Effect of impurity ions on the coupling between zonal flow and local turbulent transport in HL-2A plasmas. (1st July 2022) - Zou, Q.; Cheng, J.; Xu, Y.; Yan, L.W.; Huang, Z.H.; Wang, W.C.; Wu, N.; Xu, J.Q.; Shen, Y.; Liu, L.; Dong, C.F.; Fang, Q.; et al.
Abstract: The effect of impurity ions on the coupling between geodesic acoustic mode (GAM) zonal flow and local turbulent transport has been studied using a Langmuir probe array in HL-2A ohmically heated deuterium plasmas. The experimental results illustrate that both the frequency and amplitude level of the GAM zonal flow significantly reduce with increase in the carbon ion concentration, which is qualitatively consistent with theoretical predictions (Xie et al 2018 Plasma Phys. Control. Fusion 60 025015). Meanwhile less energy is transferred from turbulence to GAM zonal flow due to the reduction in tilting and stretching of the turbulent vortex. Consequently, the impurity ions enhance the turbulence and turbulent transport owing to the reduced GAM zonal flow, as demonstrated by experiment. The experimental results presented here therefore reveal the dual roles played by impurity ions in the dynamics of GAM zonal flow, which could contribute to the understanding of inherent mechanisms governing turbulent transport in the presence of impurity ions.